2013
DOI: 10.5604/20831862.1083275
|View full text |Cite
|
Sign up to set email alerts
|

Is Gnb3 C825t Polymorphism Associated With Elite Status of Polish Athletes?

Abstract: The GNB3 gene encodes the beta 3 subunit of heterotrimeric G-proteins that are key components of intracellular signal transduction between G protein-coupled receptors (GPCR) and intracellular effectors and might be considered as a potential candidate gene for physical performance.ObjectivesThe aim of this study was to compare frequency distribution of the common C to T polymorphism at position 825 (C825T) of the GNB3 gene between athletes and nonathletic controls of the Polish population as well as to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
2
6
1
Order By: Relevance
“…Thus, we did not corroborate the findings of Eynon et al (2009) that the GNB3 TT genotype was more frequent in endurance-oriented athletes than in sprinters. However, we confirmed the observations of Ruiz et al (2011) and Sawczuk et al (2014) in which no correlation between the frequency of alleles and genotypes of the C825T polymorphism and athletic status was observed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, we did not corroborate the findings of Eynon et al (2009) that the GNB3 TT genotype was more frequent in endurance-oriented athletes than in sprinters. However, we confirmed the observations of Ruiz et al (2011) and Sawczuk et al (2014) in which no correlation between the frequency of alleles and genotypes of the C825T polymorphism and athletic status was observed.…”
Section: Discussionsupporting
confidence: 90%
“…Research conducted on a group of top level Israeli athletes revealed a higher frequency of the genotype TT in elite endurance athletes in comparison to controls and athletes practicing strength-speed sports ( Eynon et al, 2009 ). However, the results of these observations have not been confirmed in subsequent research by Ruiz et al (2011) and Sawczuk et al (2014) .…”
Section: Introductioncontrasting
confidence: 59%
“…However, when cohorts of athletes and controls from Israeli and Spanish populations were combined (155 Israeli and 153 Spanish athletes; 240 Israeli and 100 Spanish controls), no significant differences in genotypic and allelic frequencies between countries or groups were observed [97]. Furthermore, Sawczuk et al [98] could not confirm the prevalence of the T allele in 123 Polish endurance athletes in comparison with 354 sedentary volunteers.…”
Section: Gnb3 Rs5443 T Allelementioning
confidence: 90%
“…However, some genotypes were not confirmed as genetic markers of exercise performance in the Polish population [38], and further studies are needed.…”
Section: Discussionmentioning
confidence: 99%